2011
DOI: 10.1158/0008-5472.can-10-4002
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stroma–Secreted Cytokines Protect JAK2V617F-Mutated Cells from the Effects of a JAK2 Inhibitor

Abstract: Signals emanating from the bone marrow microenvironment, including stromal cells, are thought to support the survival and proliferation of the malignant cells in patients with myeloproliferative neoplasms (MPN). To examine this hypothesis we established a co-culture platform (cells co-cultured directly [cell-on-cell] or indirectly [separated by micropore membrane]) designed to interrogate the interplay between JAK2V617F–positive cells and the stromal cells. Treatment with atiprimod, a potent JAK2 inhibitor, ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 23 publications
1
82
0
1
Order By: Relevance
“…Such cytokines are produced by the bone marrow stroma and have been shown to promote the growth of MPN clones, while, in some cases inhibiting the growth of wild-type clones. 93,94 Overexpression of NF-I, which has been described in patients with uniparental disomy (UPD) of chromosome 9, has also been suggested to result in resistance to transforming growth factor-β (TGF-β), which has been demonstrated to have inhibitory effects on the hematopoiesis and on myeloid cell lines. 95,96 The secretion of proteases which disrupt the stromal cell derived factor-1/chemokine receptor 4 (CXCR4) axis, as well as the downregulation of CXCR4 itself by tumor cells, have both been associated with greater mobilization of HSCs, and these mechanisms may contribute to extramedullary hematopoiesis and potentially mediate the loss of HSC quiescence.…”
Section: Role Of the Microenvironment In Mpn Pathogenesis And The Devmentioning
confidence: 99%
“…Such cytokines are produced by the bone marrow stroma and have been shown to promote the growth of MPN clones, while, in some cases inhibiting the growth of wild-type clones. 93,94 Overexpression of NF-I, which has been described in patients with uniparental disomy (UPD) of chromosome 9, has also been suggested to result in resistance to transforming growth factor-β (TGF-β), which has been demonstrated to have inhibitory effects on the hematopoiesis and on myeloid cell lines. 95,96 The secretion of proteases which disrupt the stromal cell derived factor-1/chemokine receptor 4 (CXCR4) axis, as well as the downregulation of CXCR4 itself by tumor cells, have both been associated with greater mobilization of HSCs, and these mechanisms may contribute to extramedullary hematopoiesis and potentially mediate the loss of HSC quiescence.…”
Section: Role Of the Microenvironment In Mpn Pathogenesis And The Devmentioning
confidence: 99%
“…Therefore, it remains to be addressed whether these differences in ST2 expression patterns rely on species-dependent divergences and whether ST2 can be also engaged on human BM stromal cells. This is relevant because humoral factors secreted by BM stromal cells may also support MPN pathogenesis by impairing compound-mediated JAK2 inhibition (11).…”
Section: Mpn Cell Lines and Cd34 + Stem/progenitor Cells From Mpn Patmentioning
confidence: 99%
“…While JAK inhibitors have been successful in treating JAK2-mutated MPNs, elimination of the mutant clone and resistance may pose an important problem, and patients with WT JAK2 MPNs are not amenable to this therapy (7). The abnormal expression and activity of a number of proinflammatory cytokines are associated with BCR-ABL1-negative MPNs (8), possibly initiating clonal evolution (9) or promoting progression to myelofibrosis (10) and resistance against JAK2 inhibitors (11). Thus, cytokines and growth factors support the aberrant hematopoiesis associated with MPNs and provide mechanisms for drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…23 A phase 2 study of INC424 in patients with relapsed/ refractory AML showed good tolerance and modest antileukemic activity. 24 Fifteen of 38 patients studied showed decreased or stabilized blasts in blood and marrow with complete remission achieved in 3 patients with prior myeloproliferative neoplasms.…”
Section: Introductionmentioning
confidence: 99%